A brain circuit of bidirectional modulation of social and nonsocial cognition by androgens and estrogens in male mice - Dario Aspesi; Anjana Varatharajah; Lucia Cioffi; Silvia Diviccaro; Donatella Caruso; Natalina Becke; Jasmin Lalonde; Melissa L. Perreault; Roberto C. Melcangi; Neil J. MacLusky; Elena Choleris (Proceedings of the National Academy of Sciences, 2026)
Androgens and estrogens rapidly influence brain function and behaviors critical to social species, including social recognition, which is essential for group living and modulating social interactions. The specific brain regions involved and their hormonal regulation remain poorly understood. This regulation is complex, as the main circulating androgen, testosterone (T), is metabolized into estrogenic (17β-estradiol, E2) and androgenic (dihydrotestosterone, DHT) compounds, meaning its actions can be mediated through both androgen (AR) and estrogen receptors (ERs). This study identifies an estrogen-regulated, social recognition-specific brain circuit, demonstrating that T and E2, but not DHT, interact with the arginine–vasopressin (AVP) system in the bed nucleus of the stria terminalis (BNST)–lateral septum (LS) pathway to promote social recognition in male mice. T, E2, and DHT all facilitated social recognition and impaired object recognition within forty minutes of infusion into the BNST, but only the effects of T and E2 were blocked by an AVP receptor 1a (V1aR) antagonist, suggesting distinct mechanisms underlie the facilitation of social recognition by estrogens and androgens. Using CRISPR/Cas9 to selectively knock down AR, ERα, ERβ, or G protein–coupled estrogen receptor (GPER) in the BNST of male mice four weeks before steroid infusion, we found that ERα and ERβ (but not GPER) are necessary for T and E2 to rapidly facilitate social recognition, whereas DHT acts through AR. Our findings highlight the distinct roles of AR and ERs in the modulation of social recognition by steroid hormones, revealing redundant and nonoverlapping mechanisms of androgens and estrogens in the functioning of the male social brain.